"I Experience Very Sharp Pain but It's On and Off": A Phenomenological Study of Postoperative Pain Experiences of Patients in Ghana - Evans Frimpong Kyei; Edward Appiah Boateng; Abigail Kusi-Amponsah Diji (Centre for Behaviour and Wellness Advocacy, 2019)
Postoperative pain has been a challenge for the healthcare industry for many years in Africa especially Ghana. However, its management has not received adequate attention like other aspects in the industry as it is evident that clients who undergo surgery continually experience much pain after surgery. The study sought to explore patients' experiences with postoperative pain management. The study employed a qualitative research design with a phenomenological approach. In all twelve (12) participants were recruited for this study using purposive sampling approach. Participants were interviewed in a face to face manner with the help of a semi-structured interview guide. These were patients who had survived more than twenty-four (24) hours after surgery. Interpretative phenomenological analysis (IPA) guided the active generation of four themes which described participants' postoperative pain management experiences. Pain disability, dualistic engagement with nurses, drivers and discomforts of analgesic intake and casting the mind off pain characterized participants' postoperative pain management experiences in the current study. Pain disability represented the debilitating nature of the postoperative pain experience which affected their activities of daily living. Participants described both positive and negative nursing encounters which were covered under the dualistic engagement with nurses. The drivers and discomforts of analgesic intake related to participants' motivation for taking prescribed pain medications and some of the untoward effects they experienced with such drugs. Casting the mind off pain illustrated participants' engagement in non-drug techniques due to their potential in distracting them from their prevailing postoperative pain. Unrelieved postoperative pain and its undesirable effects persist despite decades of advanced technologies and research on pain. Postoperative pain care should be individualized to meet the unique comfort needs of patients. Analgesics and non-drug techniques should be encouraged to maximize postoperative pain relief with minimal or no untoward effects.